2017
DOI: 10.1002/nag.2762
|View full text |Cite
|
Sign up to set email alerts
|

An efficient flexible membrane boundary condition for DEM simulation of axisymmetric element tests

Abstract: Summary The mechanical response of an assembly of particles depends on the applied boundary conditions. Robust calibration of numerical discrete systems to laboratory results is also a primary step in many studies of granular materials. In this study, a new membrane model was developed for simulating axisymmetric element tests. This membrane model uses a simple algorithm of an array of independently controlled walls and is computationally efficient. The effect of boundary flexibility on the system response was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…However, it is still observed that models with a rigid wall boundary slightly underestimate the deviator stress in the post-elastic zone compared to the simulations with a flexible membrane boundary. Similar conclusions are obtained in [10,[18][19]. The mechanism responsible for this difference is that the end restraint in our models with the flexible boundary acts as an additional confinement at the ends of the specimen, preventing the soil from moving outwards freely.…”
Section: Stress-strain Relationsupporting
confidence: 81%
See 2 more Smart Citations
“…However, it is still observed that models with a rigid wall boundary slightly underestimate the deviator stress in the post-elastic zone compared to the simulations with a flexible membrane boundary. Similar conclusions are obtained in [10,[18][19]. The mechanism responsible for this difference is that the end restraint in our models with the flexible boundary acts as an additional confinement at the ends of the specimen, preventing the soil from moving outwards freely.…”
Section: Stress-strain Relationsupporting
confidence: 81%
“…The method was initially reported by Zhao and Evans [9,11], and later Ergenzinger et al [8] reported a similar simulation method. Khoubani and Evans [10] improved the deformable ability of stacked-wall boundary further. This method is conceptually simple and easy to be implemented.…”
Section: Stacked Wallsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the sample in the triaxial test received less confinement from the lateral direction, T1 had a much lower peak stress and gentler stress softening than P1 and did not appear in the shear zone to as concentrated a degree as the latter. Khoubani and Evans performed the DEM conventional triaxial test with the cylinder flexible boundary modelled by many force‐controlled planar walls. They produced the similar shape of stress and volumetric curves to those shown in Figure for both presented dense and loose samples.…”
Section: Macro‐ and Micro‐mechanical Responsesmentioning
confidence: 99%
“…Building the membrane by bonding particles, although a widely adopted technique, causes the following problems: (1) the modelling complexity involved in shaping the membrane by particles; (2) difficulties in applying normal stress to the membrane particles according to the surface geometry; (3) an associated but unnatural friction between the membrane and soil caused by the surface asperity of the particulate membrane; and (4) an unknown relationship between the bonding parameters among membrane particles (ie, normal and shear stiffness) and the elastic parameters of the membrane (Young's modulus E and Poisson ratio v ). Alternatively, some researchers have constructed the membrane using many tiny pieces of rigid wall, served by constantly applied normal stress, to implement the hydrostatic confinement . When the membrane is separated into detached pieces of walls, this method lacks interaction and compatibility between neighbouring membrane elements, meaning that it is unable to accurately reproduce the behaviour of the membrane as an integrated entity.…”
Section: Introductionmentioning
confidence: 99%